Potential inappropriate use of strong opioid analgesics in cancer outpatients during the last year of life in France and associated factors. Issue 4 (26th August 2021) - Chu, Thanh Hang; Rueter, Manuela; Palmaro, Aurore; Lapeyre‐Mestre, Maryse
Abstract : Aims: A better knowledge of opioid prescribing patterns would help to identify areas of potential improvement in cancer pain management. This study aimed to identify potential inappropriate use (PIU) of strong opioid analgesics in cancer outpatients in their last year of life. Methods: A retrospective cohort of cancer patients who died between 2011 and 2014 and were exposed as outpatient to a strong opioid analgesic in the last year of life was identified in the Echantillon Généraliste de Bénéficiaires (a 1/97th random sample of the French general population). Prescribing patterns of strong opioids were analysed and PIU was defined by at least 1 of these criteria: overlapping prescriptions; contraindicated prescriptions; lack of laxatives; potential drug interactions; prescription in patients hospitalized for opioid‐related disorders. Factors associated with PIU were investigated through a multiple logistic regression model. Results: One third of the 2236 patients (median age 72 years [interquartile range: 61–82], 44.1% women) presented a PIU (insufficient laxative prescription [19.6% of patients], insufficient background treatment with transmucosal fentanyl [14.8%], overlapping prescriptions [2.6%]). The rate of PIU significantly decreased from 37.6% (2011) to 29.8% (2014). For patients with a duration of opioid use ≥3 months, factors associated with PIU were fentanyl prescription (adjusted odds ratio = 2.36; 95% confidence interval [1.86–3.00]) and previous use of strong opioid (adjusted odds ratio = 1.88; [1.50–2.36]). Conclusion: In France, 1/3 of cancer patients exposed to strong opioids experienced PIU and this proportion tended to decrease over time. There is still room for progress in cancer pain management at the end of life. Abstract : Potential inappropriate use of strong opioid analgesics in cancer outpatients during the last year of life in France and associated factors. Among a cohort of 2236 cancer patients who died between 2011 and 2014 and were exposed as outpatients to strong opioid analgesic in their last year of life, about 1/3 experienced potential inappropriate use of these opioids, but this proportion tended to decrease over time (from 37.64% in 2011 to 29.79% in 2014). Insufficient laxative prescription and insufficient opioid background treatment with transmucosal fentanyl were the most frequently observed. The favourable trend observed over time was mainly supported by the improvement in the coprescription of laxatives. By contrast, lack or insufficient opioid background treatment with transmucosal fentanyl was not improved over the study period.